2020
DOI: 10.1371/journal.pone.0232624
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with overweight and central obesity among adults in the Eastern Sudan

Abstract: Background A global epidemic of obesity has been documented, particularly among African countries. While central obesity and overweight have been reported for many countries, very limited information exists about the prevalence of these health problems in Sudan, and these data are nonexistent for Eastern Sudan. The present study aimed to determine the prevalence of obesity and central obesity, as well as the factors associated with both, among adults in Gadarif, Eastern Sudan. Methods A cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
7
24
5
2
Order By: Relevance
“…52 In this study, being female was found to be associated with central obesity. This finding is consistent with the studies done in Brazil, 34 Oman, 37 Eastern Sudan, 38 Northern Iran, 41 and Southern China. 53 The exact molecular link between being female and central obesity is not clearly addressed yet.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…52 In this study, being female was found to be associated with central obesity. This finding is consistent with the studies done in Brazil, 34 Oman, 37 Eastern Sudan, 38 Northern Iran, 41 and Southern China. 53 The exact molecular link between being female and central obesity is not clearly addressed yet.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with studies done in Brazil 34 and China. 35 However, our finding is lower than that of studies done in the USA, 36 Omani adults, 37 Eastern Sudan, 38 and Gondar, Ethiopia. 39 Conversely, the current finding is higher than that of the studies done in Northwest China, 40 Northern Iran, 41 India, 42 and Egypt.…”
Section: Discussioncontrasting
confidence: 74%
“…A number of studies report prevalence of abdominal obesity as 62.5% in Brazil [ 15 ], 37.6% in China [ 22 ], 58% in South Africa [ 23 ], 24.8% in Tanzania [ 24 ], and 67.8% in Sudan [ 25 ]. However, there are few studies in Ethiopia on abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension was higher than in previous three local surveys, in four states (Khartoum, Gezira, Blue Nile, and Kassala) (16.6%) [7], in the 2005-2006 Khartoum State SEPS survey (23.6%) [10], and in Khartoum State in Sudan (27.6%) [11], but lower than in two other local surveys in Gadarif, Eastern Sudan (40.8%) [8], and in four main cities of the River Nile State, north Sudan (35.7%) [9]. The prevalence of overweight/obesity (28.0%) was lower than in four states (Khartoum, Gezira, Blue Nile, and Kassala) (56.1%) [5], and in Gadarif, Eastern Sudan (59.0%) [6]. The high prevalence of inadequate fruit and vegetable intake (94.6%) in this survey was also found in a community in Kassala State, Sudan (72.8% and 36.2% rarely or did not consume fruit and vegetables, respectively) [15].…”
Section: Discussionmentioning
confidence: 57%
“…There is lack of national data on the prevalence of multiple NCD risk factors and associated factors among adults in community-based surveys in Sudan, a low-income country geographically in sub-Saharan Africa. Some population-based studies among adults in Sudan were sub-national and only focused on speci c NCD risk factors, such as the prevalence of overweight/obesity was 56.1% in four states (Khartoum, Gezira, Blue Nile, and Kassala) [5], 59.0% in Gadarif, Eastern Sudan [6], hypertension was 16.6% in four states (Khartoum, Gezira, Blue Nile, and Kassala) [7], 40.8% in Gadarif, Eastern Sudan [8], the 35.7% in four main cities of the River Nile State, north Sudan [9], 23.6% in the [2005][2006] Khartoum State STEPS survey [10], and 27.6% in Khartoum State in Sudan [11]. The prevalence of diabetes was 19.1% in four main cities of the River Nile State, north Sudan [12], 18.7% in the Northern State and River Nile State [13], and 19.8% in the 2005-2006 Khartoum State STEPS survey [10].…”
mentioning
confidence: 99%